Internet of Things (IOT) & energy harvesting for urban farming - Christiany, Janet (Nanyang Technological University, 2020)
Food security has been a concern all over the world. Singapore, despite being titled the most food secure country in the world, faces concerns too when it comes to this topic as it imports 90% of its food supply, producing only 10% locally. In order to combat possible problems of being cut off in the food supply, Singapore has to come up with ways to promote the productivity of its agricultural activity. One way is to adopt smart farming solutions that can help the farmers make better farming decisions and thereby, increases the yield of farms. However, available market solutions are often too costly for farmers to accept. With research on technologies, an alternate cheaper solution is proposed. This solution aims to help farmers manage their farms better by giving advice and insights of farming activities through various software. The report covers a research on IoT in agriculture and the different wireless communicating technologies (i.e. WiFi and Bluetooth). It also includes a documentation of the process of implementing both the hardware sensors (i.e. temperature, humidity sensors) and software applications. It concludes with the feasibility of the proposed solution in the context of Singapore, and possible future works that can be implemented to improve on the solution.